Experimental evidence sustaining a compact-extended model for doppler broadening of neutron absorption resonances - Villanueva, Alejandro Javier (2011)
Recently we presented a new model to handle solid state effects on Doppler broadening of neutron absorption resonances (DBNAR) in a simplified manner. Our model extends the commonly used effective temperature gas model (ETGM) to regions of lower energies and temperatures where the latter produces non-negligible errors; at the same time, our model reduces to the ETGM in energy and temperature regions where this model has doubtlessly proved its validity. All this is achieved with a minimum amount of information needed to describe the solid system, which is thus approximately represented by a Debye spectrum, compatible with a great degree of accuracy in the calculation. In this work a robust validation of our model is achieved when it is contrasted against experiment.